Econometric Analysis of the Impact of Domestic Rice Procurement Policy on Producer Price: The Case of Rice in Bangladesh - Mohammad A. Ashraf (Jurnal Agro Ekonomi, 2008)
IndonesianTulisan ini mempelajari secara teoritis dan praktek dari dampak kebijakan pemerintah terhadap penetapan harga gabah pada tingkat petani di Bangladesh. Pada dasarnya, kebijakan ini berupaya mencapai produksi beras dan gandum pada level harga yang ditetapkan dalam upaya memproteksi pendapatan petani dengan menstabilkan harga-harga pangan dan menyediakan pangan untuk kelompok-kelompok konsumen tertentu baik pada kondisi normal maupun tidak. Studi ini melakukan analisis ekonometrik yang menggunakan data series sepanjang 25 tahun yang dikumpulkan dari instansi pemerintah dan swasta. Hasil empirik menunjukkan bahwa petani padi tidak memperoleh keuntungan dari kebijakan ini, bahkan dalam jangka pendek sekalipun, karena adanya kesalahan potensial dari model teoritis dan pelaksanaannya. Dampaknya, intervensi pemerintah dalam upaya menjamin ketahanan pangan di masa mendatang perlu dikaji ulang untuk menetarpkan target-target yang obyektif.EnglishThis paper investigates the theoretical and practical impacts of the government procurement policy on rice producer price in Bangladesh agriculture. The policy, basically, aims at procuring a targeted amount of rice and wheat at predetermined prices in order to protect the producers’ income by stabilizing food prices and to provide foods to specified target-groups of consumers in course of normal time as well as in emergency period. The study conducted econometric analyses with twenty five years data collected from various government and private sources. The empirical finding of the study indicates that the rice producers are unlikely benefited from this policy even in the short run because of the potential caveats in the theoretical model and in its implementation. In effect, government intervention in terms of procuring food-stuffs deserves further review in order to reach its targeted objectives.